Foreign Aid and Inclusive Development: Updated Evidence from Africa, 2005-2012 - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2015)
Motivated by the April 2015 World Bank Publication on MDGs which reveals that poverty has been declining in all regions of the world with the exception of African countries, this study investigates the effects of a plethora of foreign aid dynamics on inequality adjusted human development. Contemporary and non-contemporary OLS, Fixed-effects and a system GMM technique with forward orthogonal deviations are employed. The empirical evidence is based on an updated sample of 53 African countries for the period 2005-2012.The following findings are established. First, the impacts of aid dynamics with high degrees of substitution are positive. These include aid for: social infrastructure, economic infrastructure, the productive sector and multi-sectors. Second, the effect of humanitarian assistance is consistently negative across specifications and models. Third, the effects of programme assistance and action on debt are ambiguous because they become positive with the GMM technique. Justifications for these changes and clarifications with respect to existing literature are provided. Policy implications are discussed in the light of the post-2015 development agenda. We also provide some recommendations for a rethinking of theories and models on which development assistance is based.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa